Breaking the cycle of the COVID-19 transmission: a challenge for Nigeria - Garba, Bashiru; Zakaria, Zunita; Salihu, Mohammed Danlami; Bande, Faruku; Saidu, Mohammed Bashir; Bala, Jamilu Abubakar (Edinburgh University Global Health Society, 2020)
COVID-19 has already spread to almost every country in the world, including the arctic. The impact on human health has been severe, with an increasing number of fatalities. With the spread comes economic hardship due to the preventive strategies adopted. Movement restrictions imposed in Nigeria as a result of the outbreak have generated controversies among the poor masses that depend on daily hustles to fend for themselves and their families. Nigeria being a very populous country with a high number of low-income earners who depend on their daily efforts to get food for their families, control measures like the movement restrictions and closure of business premises would have a devastating impact on them. Although the government has responded with some palliative measures, it is evident that these interventions may not be sufficient, mainly due to potential malpractices that will end up denying many supposed beneficiaries.